Physico-Chemical and Bacteriological Analyses for Evaluating the Quality of Municipal Water Supply in Kathmandu District - Karki, Parikshya; Subedee, Anup; Shakya, Bhushan (Amrit Research Journal, 2022)
Water samples from municipal water supplies in Kathmandu District were collected from 10 different sampling spots between April to May, 2018. Analyses of various physico-chemical parameters of water conducted. Physical parameters (pH, electrical conductivity, TDS) and Chemical Parameters like (total alkalinity, total Hardness, calcium, magnesium, chloride, iron, nitrate, and ammonia) were determined. This analysis was undertaken to determine whether water from municipal supply is suitable for drinking purpose or not. It indicates that in some places the municipal supplies in Kathmandu district are not suitable for drinking without filtration and proper purification.